(untitled) (Orfeu, 2022)
This article analyzes the musical formative paths of four religious and their performances as trainers within the ambit of the Catholic Church in Brazil, from the perspective of the sociology of music education. The reports were collected through interviews following a semi-structured script of questions that contemplated different aspects and themes related to the formation and performance with music in the religious environment. The Theoretical Frame of Reference elected was based on the concept of formative “paths” by José Machado Pais (2003) as the paths of formation of religious and their paths in the formation of other people. The theoretical conception of biography and the concept of formative path made it possible to connect individual practices and experiences, at the micro level, with those present in the context of the Catholic Church, at the macro level. It is understood that the musical formation of the religious interviewed is impregnated by their biographical paths revealed in the pedagogical-musical choices, forms of appropriation of musical knowledge and educational and socializing functions of religion in the context of music education.